Screening for primary aldosteronism in 1,181 Swedish primary care patients with hypertension - Makhnov, Nikita; Skov, Jakob; Åkerström, Tobias; Axling, Fredrik; Andernord, Daniel; Bergenheim, Mikael; Waldén, Mauritz; Hellman, Per (Frontiers in Endocrinology, 2025)
ObjectivePrimary aldosteronism (PA) is a common cause of hypertension. It entails elevated morbidity and mortality that do not sufficiently improve with conventional antihypertensive therapy. Screening for PA by plasma aldosterone–renin ratio (ARR) enables discovery and specific treatment of affected patients. By screening primary care patients with hypertension and evaluating them further according to the Endocrine Society guidelines, we aimed to assess the prevalence of PA, the factors affecting biochemical diagnostics, and the outcome of lateralization studies and of specific treatment of the discovered PA cases.Design, patients, and methodsProspective evaluation of screening for PA was conducted in 1,181 patients. Screening by ARR was performed under current therapy, but without mineralocorticoid receptor antagonists (MRA), under normokalemia, and confirmed by the intravenous saline suppression test, SST#1. Those with results in a defined gray zone underwent therapy adjustment and then completed SST#2. Plasma aldosterone and ARR were compared under different stages of the diagnostic process. All patients with PA were offered adrenal venous sampling, or, in certain cases, adrenocortical-specific positron emission tomography. Lateralizing cases were offered laparoscopic adrenalectomy. Patients with bilateral disease were treated with MRA. Treatment results were assessed after a minimum of 6 months.ResultsA total of 53 discovered cases of (mostly mild) PA corresponded to its prevalence of 4.5%. Initial seated ARR was higher than recumbent ARR before SST#1. At SST#2, initial ARR and final aldosterone were higher than at SST#1. Localizing studies (accepted by 45 patients) found 14 lateralized cases. Of the 11 operated cases, 4 had aldosterone-producing adenoma, and the remainder had micro- and macronodular histopathology. A total of 31 patients had bilateral PA. Both surgical and conservative treatments were well tolerated and led to improved blood pressure and higher renin, indicating risk amelioration.ConclusionsPA is prevalent among primary care patients with hypertension and can be screened for under current antihypertensive therapy. Aldosterone-producing adenoma was rare in this cohort. The study results support active screening of primary care patients with hypertension for PA in order to offer appropriate treatment options.